Managing Change in Organizations - Carnall Colin A (Prentice Hall, 1990)
This book provides a thorough and practical overview of how to achieve effective organizations. Managing Change and Creating Effectiveness, Management structures and Management in Action, Sustaining Organizational Effectiveness, Diagnosing Change, Managing Major Changes, Managing Corporate Politics, Coping with Change, managing Complexity, Leadership in Practice, Learning from Changing, A Strategy for Effectiveness.